2021
DOI: 10.1007/s13300-021-01000-6
|View full text |Cite|
|
Sign up to set email alerts
|

Baseline HbA1c Level Influences the Effect of Periodontal Therapy on Glycemic Control in People with Type 2 Diabetes and Periodontitis: A Systematic Review on Randomized Controlled Trails

Abstract: Introduction: The question of whether periodontal therapy is an effective strategy for achieving glycemic control in people with type 2 diabetes mellitus (T2DM) and periodontitis continues to be open to debate. To clarify this issue, we conducted a systematic review and meta-analysis. Methods: A systematic literature search of randomized controlled trials (RCTs) was carried out by searching four electronic databases and four journals up to April 2020. RCTs that evaluated the effect of periodontal therapy on gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 40 publications
6
24
1
3
Order By: Relevance
“…The reason why improvement in glycemic control was not achieved in our study may be because the patients' blood glucose levels at baseline were already well controlled to begin with (average HbA1c level < 7%, according to the definition of American Diabetes Association [23]). Furthermore, a systematic review indicated that the effect of periodontal treatment on glycemic control was much more obvious in studies with a higher baseline HbA1c level than in those with a lower baseline HbA1c level [43]. Another previous study indicated that the effect of lowering glucose differs based on factors such as the intervention method, duration of diabetes, baseline glycemia and whether the patient had undergone previous therapy [44].…”
Section: Discussionmentioning
confidence: 99%
“…The reason why improvement in glycemic control was not achieved in our study may be because the patients' blood glucose levels at baseline were already well controlled to begin with (average HbA1c level < 7%, according to the definition of American Diabetes Association [23]). Furthermore, a systematic review indicated that the effect of periodontal treatment on glycemic control was much more obvious in studies with a higher baseline HbA1c level than in those with a lower baseline HbA1c level [43]. Another previous study indicated that the effect of lowering glucose differs based on factors such as the intervention method, duration of diabetes, baseline glycemia and whether the patient had undergone previous therapy [44].…”
Section: Discussionmentioning
confidence: 99%
“…The slight significant continuous reduction in blood glucose level may possibly have resulted from resolution of serum inflammatory factors as well as a possible reduction of glucolipid metabolism and insulin resistance by mechanical periodontal therapy [ 51 ] or may have been due to the effect of curcumin in minimizing the increase in blood glucose level in STZ-induced diabetes rat models [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intervention studies have shown that NSPT can decrease HbA1c levels in people with DM and its efficacy is greater in patients with higher baseline HbA1c levels [ 25 , 40 , 41 , 42 , 43 ]. However, most NSPT studies were of short duration (3–6 months) because NSPT could only be delayed for a short period of time in the untreated control group for ethical reasons.…”
Section: Bidirectional Relationship Between Periodontitis and Dmmentioning
confidence: 99%